Does activation of the protective Renin-Angiotensin System have therapeutic potential in COVID-19? - Pawel Namsolleck; Gert N. Moll (BMC, 2020)
Abstract Infection of lung cells by the corona virus results in a loss of the balance between, on the one hand, angiotensin II-mediated stimulation of the angiotensin II type 1 receptor and, on the other hand, stimulation of the angiotensin II type 2 receptor and/or the Mas receptor. The unbalanced enhanced stimulation of the angiotensin II type 1 receptor causes inflammation, edema and contributes to the pathogenesis of severe acute respiratory distress syndrome. Here we hypothesize that stable, receptor-specific agonists of the angiotensin II type 2 receptor and of the Mas receptor are molecular medicines to treat COVID-19 patients. These agonists have therapeutic potential in the acute disease but in addition may reduce COVID-19-associated long-term pulmonary dysfunction and overall end-organ damage of this disease.